HIV Viral Load Trends in Six Eastern Caribbean Countries Utilizing a Regional Laboratory Referral Service: Implications for Treatment as Prevention. - R Clive Landis; Kelly Carmichael-Simmons; Ian R Hambleton; Anton Best (PLoS ONE, 2015)
Since 2009, seven countries in the Organization of Eastern Caribbean States (OECS), Antigua & Barbuda, Dominica, Grenada, Montserrat, St. Kitts & Nevis, Saint Lucia, and St. Vincent & the Grenadines, have been utilizing a laboratory referral service for HIV-1 viral load (VL) offered by The Ladymeade Reference Unit (LRU) Laboratory, Barbados. The objective of this study was to evaluate 5 year VL trends in the six larger OECS countries participating in this regional referral service.Blood samples were collected in source countries and transported to Barbados as frozen plasma according to a standardized protocol. Plasma specimens were amplified by RT PCR on a Roche TaqMan 48 analyser (Roche Diagnostics, Panama City, Panama). VL was considered optimally suppressed below a threshold level of < 200 HIV-1 copies/mL of blood. The same threshold was used as a binary indicator in an analysis of the secular change in VL suppression. Montserrat was excluded due to insufficient number of samples.A steady rise in VL referrals from OECS countries was recorded, rising from 312 samples in 2009 to 1,060 samples in 2013. A total of 3,543 samples were tested, with a sample rejection rate (9.2%) mostly due to breaks in the cold chain. Aggregate VL data showed the odds of VL suppression in the Eastern Caribbean improved by 66% for each additional year after 2009 (Odds Ratio 1.66 [95% CI 1.46 to 1.88]; p<0.001).We demonstrate the feasibility of establishing a regional laboratory referral service for HIV VL monitoring in the Eastern Caribbean. Aggregate VL trends showed a significant year-on-year improvement in VL suppression, implying public health benefits through treatment as prevention in the OECS. VL provides a powerful monitoring & evaluation tool for strengthening HIV programs at country level among the small island states participating in this regional referral network.